Learning to Fail Better: Reflections on the Challenges and Risks of Community-Based Participatory Mental Health Research With Inuit Youth in Nunavut - Polina Anang; Nora Gottlieb; Nora Gottlieb; Suzanne Putulik; Shelley Iguptak; Ellen Gordon (Frontiers Media S.A., 2021)
Community-based participatory research (CBPR) is a mine field of moral dilemmas. Even when carefully planned for and continuously critically reflected upon, conflicts are likely to occur as part of the process. This paper illustrates the lessons learned from "Building on Strengths in Naujaat", a resiliency initiative with the objective of promoting sense of belonging, collective efficacy, and well-being in Inuit youth. Naujaat community members over time established strong meaningful relationships with academic researchers. Youth took on the challenge of organizing community events, trips out on the land, and fundraisers. While their creativity and resourcefulness are at the heart of the initiative, this paper explores conflicts and pitfalls that accompanied it. Based on three themes - struggles in coming together as academic and community partners, the danger of perpetuating colonial power structures, and the challenges of navigating complex layers of relations within the community - we examine the dilemmas unearthed by these conflicts, including an exploration of how much we as CBPR researchers are at risk of reproducing colonial power structures. Acknowledging and addressing power imbalances, while striving for transparency, accountability, and trust, are compelling guiding principles needed to support Indigenous communities on the road toward health equity.